Problems of Using Blockchain-based Smart Contracts in Standardizing Mineral Commodity Sale and Purchase Agreements - Sri Wisnuaji; Hidayati Hidayati (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2026)
The development of blockchain technology and smart contracts has presented a new paradigm in contract practice, including in mineral commodity sales and purchase transactions, which are highly complex and potentially subject to significant disputes. This study aims to analyze the legal status of smart contracts in the Indonesian legal system, identify the challenges to their application in the mining sector, and formulate a legal framework that adapts to technological developments. The method used is a normative juridical approach, employing statutory, conceptual, and comparative analyses of the Civil Code, the Electronic Information and Transactions Law, and mining regulations. The results of the study indicate that smart contracts do not fully meet the requirements of contract law, particularly regarding consent and the parties' understanding of the code. Furthermore, there are conflicts with contractual principles such as good faith and flexibility in the face of force majeure. The implications for the concepts of default and legal liability have also shifted due to the automated nature of smart contracts. Nevertheless, this technology has the potential to increase transaction efficiency and transparency. This study recommends a hybrid contract model that combines legal codes and texts, and also calls for regulatory harmonization to accommodate the use of smart contracts in the mining sector.